A study of electric field components in shallow water and water half-space models in seabed logging - Rostami, A. (American Institute of Physics Inc., 2016)
Seabed logging (SBL) is an electromagnetic (EM) method to detect hydrocarbon (HC) laid beneath the seafloor, which is a development of marine controlled source electromagnetic (CSEM) method. CSEM is a method to show resistivity log of geological layers, transmitting ultra-low frequency EM wave. In SBL a net of receivers, placed on the seafloor, detect reflected and refracted EM wave by layers with different resistivity. Contrast of electrical resistivity of layers impacts on amplitude and phase of the EM wave response. The most indispensable concern in SBL is to detect guided wave via high resistive layer under the seafloor that can be an HC reservoir. Guided wave by HC creates a remarkable difference in received signal when HC reservoir does not exist. While the major contribution of received EM wave in large offset, especially in shallow water environment, is airwave, which is refracted by sea surface due to extremely high resistivity of atmosphere, airwave can affect received guided wave, dramatically. Our objective for this work is to compare HC delineation of tangential and normal components of electric field in shallow water area, using finite element method simulation. Will be reported that, in shallow water environment, minor contribution of air wave in normal component of E field (Ey) versus its major contribution in the tangential component (Ex), causes a considerable contrast on HC delineation of Ey for deeply buried reservoirs (more than 3000 m), while Ex is unable to show different contrasts of received data for with and without HC media at the same condition. Â© 2016 Author(s).